Visualization of patient's knee movement and joint contact area during knee flexion for orthopaedic surgery planing validation. Issue 3 (4th May 2021) - Mercader, Alexandra; Roettinger, Heinz; Bigdeli, Amir; Lueth, Tim C.
ABSTRACT: The high number of revision surgery by total knee replacement to reduce joint pain shows the complexity of the procedure and the current difficulties to make the right diagnosis. This work presents a joint contact area visualization during a recorded flexion and extension of the knee to improve the understanding of the knee kinematics before and after the operation. The position of the patient's bones is registered using two trackers, one placed on the upper leg and one on the lower leg. The movement of the knee joint is recorded with an infrared stereo camera. Thanks to a visualization software, the doctor can spontaneously observe the pressure zones at the joint and the movement of the bones recorded from live measurements. The visualization of contact areas together with the patient's bone's geometry helps for patient diagnosis. The kinematics of the knee flexion brings more information on the validity of the flexion movement before and after surgery, enabling the two to be compared as well as separately analysed. The contact areas can also be compared pre- and post-operatively, or between right and left knees. The accuracy of the visualization software has been tested using a 3D phantom model of a knee joint.